Holocene climate change and anthropogenic activity records in Svalbard: a unique perspective based on Chinese research from Ny-Ålesund - Zhongkang, Yang; Linxi, Yuan; Yuhong, Wang; Liguang, Sun (Polar Research Institute of China - PRIC, 2017)
Climate change in the Arctic region is more rapid than that in other areas owing to Arctic amplification. To better understand climate change and the driving mechanisms, long-term historical reconstructions throughout the Holocene and high-resolution records of the past few hundred years are required. Intense anthropogenic activities in the Arctic have had a great impact on the local environment. Here, we review the Holocene climate change record, responses of the ecosystems to climate change, and the anthropogenic impacts on the environment based mainly on Chinese research from Ny-Ålesund. Climate reconstruction studies from Svalbard have revealed several cold episodes during the Holocene, which are consistent with ice rafting events in the North Atlantic region and glacier activity from Greenland, Iceland, and Svalbard. The ecosystem also showed corresponding responses to climate change, especially during the late Holocene. Over recent decades, anthropogenic activities have caused serious pollution and deterioration to the local environment in Svalbard in areas frequented by people. Greater environmental protection is therefore needed to reduce the anthropogenic impacts on the local environment.